Stereoselective syntheses of (+)-proto, (-)-gala quercitols and carba-L-rhamnose from D-(-)-quinic acid - Murugan, A. Vadivel; Yadav, A. K.; Gurjar, M. K. (Tetrahedron Letters, 2005)
Efficient syntheses of (+)-proto, (-)-gala quercitols and carba-L-rhamnose front D-(-)-quinic acid are described. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: (+)-proto quercitol; (-)-gala quercitol; carba-L-rhamnose; cyclohexanepentols; D-(-)-quinic acid; stereoselectivity